2020
DOI: 10.2174/1566524019666191105150709
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrogen-rich Water on the PI3K/AKT Signaling Pathway in Rats with Myocardial Ischemia-reperfusion Injury

Abstract: Background: The effects of hydrogen-rich water on PI3K/AKT-mediated apoptosis were studied in rats subjected to myocardial ischemia-reperfusion injury (MIRI). Methdos: Sixty rats were divided randomly into a hydrogen-rich water group and a control group. The hearts were removed and fixed in a Langendorff device. Hearts from the control group were perfused with K-R solution, and hearts from the hydrogen-rich water group was perfused with K-R solution + hydrogen-rich water. The two treatment groups were then d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Additionally, Terasaki and colleagues reported that H 2 can downregulate the gene expression of proapoptotic Bax and inhibit its translocation to mitochondria by an unknown mechanism [ 39 ]. H 2 can also inhibit apoptosis by activating the phosphatidylinositol-3-kinase/protein kinase B (PI3K/AKT) and the Janus kinase 2/signal transducer and activator of transcription 3 (JAK2-STAT3) signaling pathways in rats with myocardial ischemia-reperfusion injury (MIRI) [ 40 , 41 ], as well as downregulating the p38 MAPK signaling pathway in rat models with lipopolysaccharide- (LPS-) induced acute lung dysfunction [ 42 ] and cerebral ischemia-reperfusion injury (CIRI) [ 43 ]. Interestingly, Wang et al recently discovered that H 2 inhibited the growth, migration, and invasion of the A549 and H1975 lung cancer cell lines and promoted cell apoptosis, suggesting that H 2 might play crucial roles in the treatment of lung cancer [ 44 ].…”
Section: Mechanisms Of the Action Of Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Terasaki and colleagues reported that H 2 can downregulate the gene expression of proapoptotic Bax and inhibit its translocation to mitochondria by an unknown mechanism [ 39 ]. H 2 can also inhibit apoptosis by activating the phosphatidylinositol-3-kinase/protein kinase B (PI3K/AKT) and the Janus kinase 2/signal transducer and activator of transcription 3 (JAK2-STAT3) signaling pathways in rats with myocardial ischemia-reperfusion injury (MIRI) [ 40 , 41 ], as well as downregulating the p38 MAPK signaling pathway in rat models with lipopolysaccharide- (LPS-) induced acute lung dysfunction [ 42 ] and cerebral ischemia-reperfusion injury (CIRI) [ 43 ]. Interestingly, Wang et al recently discovered that H 2 inhibited the growth, migration, and invasion of the A549 and H1975 lung cancer cell lines and promoted cell apoptosis, suggesting that H 2 might play crucial roles in the treatment of lung cancer [ 44 ].…”
Section: Mechanisms Of the Action Of Hmentioning
confidence: 99%
“…In addition to treating atherosclerosis, H 2 reduces MIRI, which refers to a heart lesion that develops upon the resumption of the flow of oxygen-rich blood after a period of ischemia and which usually occurs during acute myocardial infarction or open-heart surgery [ 40 , 90 ]. A recent series of studies by Li et al found that HW inhibited cardiomyocyte apoptosis by activating the PI3K/AKT and JAK2-STAT3 signaling pathways and can also reduce the level of oxidative stress in myocardial tissue by upregulating the expression of the nuclear erythroid 2-related factor 2/antioxidant response element (Nrf2/ARE) signaling pathway, which alleviated I/R injury in isolated rat hearts [ 39 , 40 , 91 ]. Other studies demonstrated that intraperitoneal injection of HW before reperfusion significantly decreased the concentration of malondialdehyde (MDA) and infarct size, as well as reducing myocardial 8-OHdG and the levels of TNF- α and IL-1 β in an area at risk zones [ 92 , 93 ].…”
Section: Preventive and Therapeutic Applications Of H 2 mentioning
confidence: 99%
“…Reperfusion therapy, while crucial in ischemic heart disease (IHD) treatment, paradoxically contributes to MIRI in clinical therapy. 20,21 More recently, several studies indicated that limiting reperfusion injury prevents microvascular obstruction and reduces final infarct size, thereby lowering the probability of heart failure events and improving quality of life in AMI patients. 22 Our study delves into the relationship between PEDF, Nrf2 and ferroptosis, investigating their potential therapeutic roles in MIRI.…”
Section: Discussionmentioning
confidence: 99%
“…First, it phosphorylated the PIP2 for the production of PIP3, subsequently, it activated the Akt, activating the downstream targets and promoting apoptosis [35,36]. Li et al discovered that the hydrogen-rich water activated the PI3K-Akt signaling pathway, reduced the ischemia/reperfusion injury of the isolated rat hearts, and inhibited the apoptosis of the myocardial cells [37]. The TNF was found to bind to two types of receptors, TNFR1 and the TNFR2.…”
Section: Discussionmentioning
confidence: 99%